2015
DOI: 10.1038/nrclinonc.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical overview of metronomic chemotherapy in breast cancer

Abstract: Over 15 years ago, low-dose metronomic chemotherapy was shown to induce disease control in patients with advanced-stage breast cancer with a lower incidence of adverse events compared with conventional maximum tolerated dose chemotherapy. Good response rates have been seen in heavily pre-treated patients for whom limited treatment options are available. Most patients prefer oral therapy and metronomic chemotherapy is a convenient alternative in patients with advanced-stage disease in which minimal toxicity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 125 publications
0
96
0
2
Order By: Relevance
“…Munzone et al summarized some ongoing clinical trials and the forthcoming results may be helpful [2,15]. Meanwhile, according to the principles of precision medicine, prognosis factors such as vascular endothelial growth factor (VEGF), serum HER-2 and EGFR, endothelial nitric oxide synthase (eNOS), thrombospondin-1 (THBS-1), circulating endothelial cells (CECs), and gene polymorphism should be considered for patient selection to standardize MCT [18,26,28,32,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Munzone et al summarized some ongoing clinical trials and the forthcoming results may be helpful [2,15]. Meanwhile, according to the principles of precision medicine, prognosis factors such as vascular endothelial growth factor (VEGF), serum HER-2 and EGFR, endothelial nitric oxide synthase (eNOS), thrombospondin-1 (THBS-1), circulating endothelial cells (CECs), and gene polymorphism should be considered for patient selection to standardize MCT [18,26,28,32,43].…”
Section: Discussionmentioning
confidence: 99%
“…Another MCT study showed weekly paclitaxel dosing resulted in a higher complete response (CR) rate compared to a standard 3-week schedule [14]. A series of single-arm, phase II clinical trials involving the various types of chemotherapeutic agents used in MCT have been conducted [15]. However, the results of these research studies have been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, intermittent doses (i.e., drug holidays) failed to control tumor growth (122). Indeed, low-dose maintenance regimens have long been evaluated in clinical practice (125); however, evidence showing the control of tumor evolution through metronomic approaches in patients is lacking. In this setting, measuring tumor evolution could offer additional criteria to assess the efficacy of complex regimens and possibly to model more effective sequences of induction and maintenance therapy for solid tumors.…”
Section: Reviewmentioning
confidence: 98%
“…Many studies showed that LDMC used for palliation can achieve disease control and prolonged overall survival without severe side effects [7]. Over the last decade, clinicians have begun to consider introducing LDMC much earlier into the treatment plan [8,9]. In comparison with conventional chemotherapy, the lower doses of LDMC may induce fewer side effects [10,11,12,13], which may lead to a lower rate of discontinuation due to side effects such as myelosuppression [10].…”
Section: Introductionmentioning
confidence: 99%